Migration in the Time of COVID-19—Policy Responses and Practices in Croatia Concerning the Western Balkan Routes and Readiness for the Post-COVID-19 Society in Which the Right to Health Care for the Most Vulnerable Is Guaranteed - Roksandić, Sunčana; Mamić, Krešimir; Mikac, Robert (Frontiers in Human Dynamics, 2021)
This Research Paper aims to provide answers on how COVID-19 pandemics influenced migration law, policy responses and practices in Croatia, particularly concerning migrants on the Western Balkan route. Throughout the EU, governments have reinstituted border controls in the Schengen region and any ‘non-essential travel’ to the EU has been suspended. In this paper, it is analyzed whether asylum seekers have been denied entry in violation of international refugee law and whether immigration officers held detainees because of the risks posed by COVID-19 alongside Croatian borders. In addition, the paper addresses the question whether and to what degree the COVID-19 pandemic influenced the overall approach towards migrants and their access to services, primarily the right to health care. Also, it is researched whether facilities for migrants and asylum seekers have appropriate health care and whether the measures imposed by the Croatian Institute of Public Health and by the National Emergency Response Team are respected when dealing with migrants. In addition, it is researched whether the EU, UN, WHO policies and recommendation concerning COVID-19 and migrants, where applicable, are respected in Republic of Croatia and whether specific policies concerning migrants and COVID-19 were introduced. All legislation, policy responses and practices will be critically approached and examined. The text will make proposals for implementation of best practices and policy responses for migrants in the context of COVID-19. All statistical data that are necessary for this research are requested from the Ministry of Interior of the Republic of Croatia.